Peran Pengasuhan Konselor dalam Membentuk Karakter Positif Peserta Didik di Sekolah - Azam Syukur Rahmatullah (Universitas Pancasakti Tegal, 2021)
This study examines the role of a counselor in school for establish the behavior of a student to be positive. So far, a counselor is considered as scary monster for students and provides less intense care for students, so that the care provided is not optimal and even tends not to be included in the actual parenting criteria. This research is a library research, which examines through writings related to counseling guidance in schools. Researchers seek to explore works related to research on counseling guidance. The results obtained are that the need for nurturing a counselor who is sincere, attached, and enriched with unconditional love, which is full of love, intimacy, friendship, and is able to enlighten the students, which in the end will be able to bring students towards positive character behavior. With this, there is a need for consistent and continuous care, not the type of care that is only temporary, or just seems like a mere formality, because with this consistent nature of care, it will produce students who are healthy, and able to function fully. It is different if what is put forward is care that is temporary in nature, will make children return to unproductive behavior, and behavior that is not positive in character.